The Cognitive, Behavioral, and Emotional Aspects of Eating Habits and Association With Impulsivity, Chronotype, Anxiety, and Depression: A Cross-Sectional Study - Aoun, Carla; Nassar, Lynn; Soumi, Stéphanie; El Osta, Nada; Papazian, Tatiana; Rabbaa Khabbaz, Lydia (Frontiers in Behavioral Neuroscience, 2019)
Background and objectives: Understanding behavioral issues associated with eating would provide important insight into obesity development and possibly procure ways to prevent its occurrence or to treat it. This study’s objectives were to examine links between cognitive, behavioral and emotional aspects of eating habits and chronotype, impulsivity, anxiety and depression among university students. Subjects and methods: The following questionnaires were used: TFEQ-R 18, UPPS-short, HADS and MEQ. Informed written consent was obtained from all 400 individuals participating in the study. Results: The results showed significant associations between the 3 dimensions of eating habits (cognitive restraint CR, uncontrolled eating UE and emotional eating EE) and BMI. UE and EE were correlated to an increase in BMI which was associated with a higher CR. No differences in CR or UE were observed in this study between males and females; only EE was significantly higher among females. Impulsivity was intimately associated to eating habits. Higher sensation seeking was associated to lower CR and higher negative urgency was associated with higher UE and EE in this study. an increased BMI was observed among persons with higher lack of premeditation and higher lack of perseverance. Morning type individuals had higher CR while evening type individual presented higher UE scores. Anxiety and depression scores were not significantly correlated to any of the 3 factors of eating habits. Conclusions : our results showed significant associations between the 3 dimensions of eating habits (CR, UE and EE) and BMI and highlight the fact that CR relation to BMI is different from EE and UE. Significant correlations between eating habits and two major impulsivity domains (sensation seeking and negative urgency) were observed. Chronotype also plays a key role in determining CR and UE and morning type individuals had higher CR while evening type individuals presented higher UE scores.